Editorial to the Issue on Populism and the Remaking of (Il)Liberal Democracy in Europe - Rensmann, Lars; Lange, Sarah L. de; Couperus, Stefan (2017)
Abstract: Populism has become the issue of comparative political science today. The rise and continuing success of populist parties is by now evident across Europe, despite persistent cross-national variations. Populist parties' electoral success and their participation in government have raised questions about their impact: not just on established party systems, but also on the systemic core of European democracies. In theory, this impact can be both beneficial for, as well as a challenge to democracy in general, and the tenets of liberal constitutional democracy in particular. The presence of populist parties has, in several cases, increased electoral turnout and public participation, which is generally seen as a positive effect when measuring the quality of democracy. However, populist parties' rise also points to negative effects. In addition to profoundly reshaping European party systems, they advocate what the populist Hungarian prime minister Viktor Orbán calls "illiberal democracy".